Mentoring for beginning teachers and sustainable improvement of teaching practices - Reséndiz Melgar, Norma Nélida (Avances en Supervisión Educativa, 2023)
The purpose of this article is to contribute to reflection on the relationship between tutoring or mentoring of beginning teachers and the improvement of their teaching practices. To do this, it addresses what is meant by educational improvement, how it is evidenced and how it can be strengthened so that it is sustainable over time and institutionally, considering the pedagogical core of teaching proposed by Elmore and the skills required for the future. All this within the framework of a practical-reflexive knowledge as the basis of the tutorial. Finally, elements of a teaching based on collegiality and mutual learning that contribute to such improvement are discussed.